The Performance of Some Walnut (Juglans regia) Cultivars in the Conditions of Bursa, Turkey - Özlem Utku; Mevlüt Batuhan Koşar; Cevriye Mert; Dilan Ahı Koşar; Umran Ertürk (Journal of Agricultural Sciences)
The present study aimed to evaluate the pomological and phenological traits, as well as yield potential and incidence of external defects of some local (‘Bilecik’, ‘Maraş 12’, ‘Maraş 18’, ‘Şebin’, ‘Şen 1’) and foreign (‘Chandler’, ‘Fernette’, ‘Fernor’, ‘Howard’, ‘Pedro’, ‘Serr’) walnut cultivars grown in Bursa (north-west in Turkey) conditions between 2014 and 2020. The first leafing was observed in Maraş 12, Serr, Şebin, and Maraş 18 cultivars, while Fernette and Fernor were the last leafing cultivars. The female blooming period of the cultivars was recorded to be the longest in Maraş 18 (15 days) and Şebin (16 days) and that was the shortest in Bilecik and Serr (10 days). The male blooming period was recorded as the longest in Chandler, Fernette, Bilecik, and Şebin (16-18 days) and that was the shortest in Maraş 12 and Serr (10 days). The average yield per tree of cultivars ranged between 1.87 kg (Şebin) and 14.21 kg (Pedro). Walnut blight was observed on average in 15.85%, sunburn in 10.21%, codling moth in 5.11%, anthracnose in 3.23%, and bird damage in 2.35% of the fruits. The healthy nut percentage ranged from 40.06% (Şen 1) to 76.50% (Chandler). The nut weight of cultivars was between 9.91 g (Maraş 12) and 16.27 g (Şen 1). Kernel percentage varied from 36.31% (Şen 1) to 53.56% (Maraş 12). The principal component analysis conducted to distinguish the cultivars suggests that the most important factors could be reduced to five components. The results showed that Maraş 12, Chandler, Fernor, and Howard were suitable cultivars for commercial cultivation in Bursa conditions.